The Impact of the 15-Minute Reading Program on the Reading Culture of Elementary School Students - Lestari, Indah Ayu; Ramadan, Zaka Hadikusuma (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to describe the impact of the 15-minute reading program on the reading culture of fifth-grade students at SDN 023 Pandau Jaya in the Siak Hulu District of Kampar Regency. The methodology employed in this research is a qualitative approach utilizing a case study method. There are two types of data sources: primary and secondary. Primary data is derived from original information collected directly by the researchers through observations, interviews, and documentation involving class teachers and fifth-grade students at SDN 023 Pandau Jaya. Meanwhile, secondary data were obtained from journals, books, supporting documents, and notes relevant to the research. The researchers employed various techniques for data collection, including interviews, observations, and document reviews involving research subjects such as the principal, the VB homeroom teacher, and the VB class students in elementary schools. The data analysis technique used in this study was based on the Miles and Huberman model, which consists of data reduction, data presentation, and drawing conclusions. The results of the study indicated that the 15-minute reading program had both positive and negative impacts on the reading culture of fifth-grade elementary school students. Positive impacts included the encouragement of a reading culture, while negative impacts included the perception of reading as an obligation rather than a necessity, which led to feelings of pressure among students regarding the 15-minute reading program activities conducted in elementary schools.